Encyclopedia of children and childhood in history and society - Fass, Paula S. (Gale virtual reference library, 2004)
"Readers are assured the latest interdisciplinary scholarship from an emerging field of study that examines the social history of children and childhood. Some 445 expertly written articles bring new insight and understanding about the lived experiences of children and the many complex cultural meanings ascribed to childhood. Emphasizing social history yet treating a broad range of related topics, the set also contains a thematic outline of contents, comprehensive index, and appendix that lists important primary sources."--"Reference that rocks," American Libraries, May 2005.